2019
DOI: 10.1049/el.2019.2650
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of target distortion in pulse‐agile sensors via Richardson–Lucy deconvolution

Abstract: Pulse-agile radar systems are becoming more prevalent as the demand for adaptive and cognitive systems increases. This focus is motivated by the need for interference avoidance and spectrum sharing. Pulse agility within a coherent processing interval (CPI) or intra-CPI adaption has been shown to cause distortion, which will negatively impact the radar's performance. This problem can be framed in the context of image processing such that an ideal range-Doppler image is corrupted by some point spread function. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…The target is much more visible when the DQN-established policy is utilized compared to the policy iteration approach, as the processed data being more coherent. While distortion effects from cognitive radar transmissions may be corrected by signal processing techniques, such as the Richardson-Lucy deconvolution algorithm or non-identical multiple pulse compression (NIMPC) [41], [42] the DQN approach may mitigate the need for computationally expensive post-processing.…”
Section: A Experimental Resultsmentioning
confidence: 99%
“…The target is much more visible when the DQN-established policy is utilized compared to the policy iteration approach, as the processed data being more coherent. While distortion effects from cognitive radar transmissions may be corrected by signal processing techniques, such as the Richardson-Lucy deconvolution algorithm or non-identical multiple pulse compression (NIMPC) [41], [42] the DQN approach may mitigate the need for computationally expensive post-processing.…”
Section: A Experimental Resultsmentioning
confidence: 99%
“…Compared with the usual Richardson-Lucy, the special case has many advantageous characteristics. The speed of iterative deconvolution in the paper is much faster than the usual one whose iterative speed is lower than the Wiener filter [23]. Moreover, due to the iterative time reversal can focus more and more energy on the strongest target, the peak-signal power of the iterative deconvolution is higher and higher with the number of iteration increasing.…”
Section: Introductionmentioning
confidence: 93%
“…Recent publications have shown that deconvolution-based methods can yield higher resolution and higher processing gain than the conventional methods, such as the CLEAN algorithm [12], Wiener filter [16] and Richardson-Lucy algorithm [21][22][23][24][25]. The Richardson-Lucy algorithm was devised by Richardson [26] and Lucy [27], which is an iterative deconvolution algorithm and recently applied in active radar/sonar to remove the blur caused by the transmitted signal [23][24][25]. In [23,24], the Richardson-Lucy algorithm is applied to the range-Doppler image, whereas it is used to the range image in the case of zero-Doppler in the paper.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major challenge for frequency agile cognitive radar systems is target distortion in the range-Doppler processed data as a result of clutter modulation from intra-CPI pulse adaptations [9]. RL-based radar control is useful to mitigate this problem since radar behavior is motivated through a human-defined reward mapping.…”
Section: Introductionmentioning
confidence: 99%